The Role of Organizational Culture in Building a Learning Organization From the Point of View of Employees in Government Agencies in Saudi Arabia - Abdelbasit, Tilal (The Arab Journal of Administration, 2022)
The study aimed to identify the role of organizational culture in building learning government agencies organization in the Kingdom of Saudi Arabia. To achieve the objective of the study, a descriptive and analytical approach was used the study population consisted of all the trainees of the Institute of Public Administration is an employee working in government agencies in Saudi Arabia.500 questionnaires were distributed to a random sample, and 417 questionnaires were received, they were all valid for analysis. The study has reached several results of the most important as follows: The elements of organizational culture are moderately available at an average degree of (3.3(in the governmental agencies in the Kingdom of Saudi Arabia. The organization building systems provide medium degree of (2.7) in the- learning governmental agencies in the Kingdom of Saudi Arabia, and have strong links. There is an inverse correlation between the prevailing organizational culture with the government agencies in Saudi Arabia and the building systems of the learning organization. The correlation coefficient has reached (-0.782), that is, the more organizational culture reduces the building of the organization’s learning systems, the researcher attributes this reason to the weak link between (organizational values, beliefs) and also to the weak link between (technology and learning). The study recommendations were as follows: Raising the level of organizational culture in government agencies by focusing on strengthening organizational values ​​and beliefs. and adopting the participating leadership style, and applying total quality management in the public sector. Raising the level of building systems of the learning organization by focusing on applying the Marquaradt model to build the educated organization with its five elements, and making measurements for each component. Organizing workshops aimed at consolidating organizational values ​​by rewriting the value charter for each government agency, defining a mechanism for monitoring its application, linking it to organizational beliefs and expectations and measuring that, to strengthen the link that contributes to building the learning organization. Relationship that contributes to the building of the organization’s learning systems.